Foreword - Journal, HEROS (Helsinki Romanian Studies Journal, 2024)
The Lectureship in Romanian Language and Culture at the University of Helsinki (the Faculty of Arts, the Department of Languages), in collaboration with the University of Helsinki Library, and the Romanian Language Institute in Bucharest, is honored to present the inaugural issue of HEROS Journal (Helsinki Romanian Studies Journal). This publication is dedicated to fostering Romanian Studies and aims to establish a dynamic platform for scholarly dialogue. It seeks to engage both experienced academics and emerging researchers, while continuing the editorial legacy of the Finnish Journal for Romanian Studies (2015–2018), previously published by the University of Turku. As a young and ambitious academic journal, HEROS aspires to promote rigorous intellectual exchange across a broad spectrum of topics within Romanian Studies. Emphasizing interdisciplinarity and inclusivity, the journal welcomes research articles that go beyond traditional fields such as Romanian language, literature, and cultural studies, and embrace diverse disciplines and methodologies. The current issue features a rich selection of articles addressing topics ranging from Romanian philosophy, history, and society, to language, culture, literature, and cinema. These contributions offer fresh, thought-provoking perspectives and foster dialogue between Romanian and other linguistic and cultural contexts. We extend our deepest gratitude to the contributors for their valuable insights and original research, and to the peer reviewers for their meticulous evaluations and critical contributions to the quality of this issue. Their dedication not only ensures the journal’s academic rigor but also plays a vital role in building and strengthening the HEROS community of researchers committed to advancing the field of Romanian Studies. The Editors